High-Statistics Study of the β+/EC-Decay of 110In - Varela A. Diaz (EPJ Web of Conferences, 2014)
A study of the 110In β+/EC decay was performed at the TRIUMF Isotope Separator and Accelerator (ISAC) facility to probe the nuclear structure of 110Cd. The data were collected in scaled-down γ-ray singles, γ − γ coincidence, and γ-electron coincidence mode. The data were sorted and a random-background subtracted γ − γ matrix was created containing a total of 850 million events. We expanded the level scheme of 110Cd significantly by identifying 75 levels under 3.8 MeV, including 12 new ones, and increased the number of previously observed transitions from these levels to 273. The γ-ray branching intensities have been extracted through an analysis of the coincidence intensities. The branching ratios were combined with a reanalysis of lifetimes measurements obtained in an (n, n'γ) reaction with monoenergetic neutrons for the calculation of B(E2) values and these results have lead to the proposal of a γ-soft rotor, or O(6) nucleus, rather than a vibrational, or U(5) pattern for the nature of the low-lying, low-spin levels in 110Cd.